IMPLEMENTATION OF E-COMMERCE IN PERCETAKAN CITRA BERSAMA TANJUNGBALAI USING THE CRM METHOD - Nurhikma Ritonga; Neni Mulyani; Rika Nofitri (Kresnamedia Publisher, 2022)
Citra Bersama Tanjungbalai Printing is a business engaged in selling printing products and services, established in 2006, located on Jalan Peninsula, Sirantau Village, Datuk Bandar District, Tanjungbalai City. The problems that occur in Citra Bersama Printing are not yet implementing an online sales system; customers have difficulty knowing sales information on the printing press. There is no information system to carry out promotions, and recording customer order data at the printing press is still done manually. Therefore, the E-commerce application uses the CRM method of web-based product sales and printing services to help buyers find various information and make it easier for buyers to place orders without coming directly to the printer. The application of E-commerce with the CRM method helps Tanjungbalai Citra Bersama Printing in conducting promotions and providing information related to the sale of products and services marketed to customers, as well as expanding sales of products and services sold due to promotional features, discount prices, customer data, live chat, and product ratings.